Religious Moderation in Islamic Boarding Schools: Prof. KH Yudian Wahyudi's Pancasila Ideology Thought to Oversee Religious Moderation in Islamic Boarding Schools - Chasanah, Iflahathul; Mawardini, Intan Dewi; Mustaqim, Azmi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
Religious moderation has several pillars that must be understood and studied by those living in Indonesia. In religious moderation, indicators as a determinant of loving the homeland or NKRI are set in stone, one of which is believing and believing in Pancasila as the basis of the country which has been upheld with various values contained which are very meaningful. With the ideology of Pancasila, which is an indicator of religious moderation, it is hoped that Islamic boarding schools in Indonesia will be able to become one of the best implementing agents and be able to harmonize the teachings and values of this ideology with the students. Because the education system in Islamic boarding schools produces students who are committed to their religious teachings which put religion as the soul and preaching as a way of controlling the soul. Therefore, Islamic boarding schools are expected to be able to adopt an intolerant attitude towards religious commitments and perspectives on life in a country, especially Indonesia, which consists of the Unitary State of the Republic of Indonesia and Pancasila.KH Yudian Wahyudi has a very important point of view in grounding the values of Pancasila, diversity, tolerance, democracy, justice, nationality, love for the motherland, and love for peace. And through Islamic boarding school education that upholds religion and faith, it is hoped that it can become one of the agents who live by the values of Pancasila as a national ideology that has philosophical values about divinity, justice and respect for fellow human beings to be a good starting point to be implemented as best as possible in the scope of Islamic boarding schools specifically to oversee religious moderation. So that religious moderation can be maintained properly in accordance with Pancasila which is the basis of the Republic of Indonesia.